The role of fiscal control in reducing tax evasion - Salman, Sheeyma (Humanities Journal of University of Zakho, 2022)
The research aims to verify the role of fiscal control in tax evasion. The research community included employees in tax departments in Dohuk Governorate. The study relied on the questionnaire form as a main tool for collecting field data. The sample included (57) employees in those departments, and the data was analyzed through Spss programs and using statistical tools, the sample opinions were analyzed about the research variables The research concluded that there are moral levels of tax evasion among taxpayers in the governorate and the existence of an inverse correlation between each of the fiscal control and tax evasion, as the fiscal control has a moral effect in reducing the levels of tax evasion, and the study recommended the need to pay attention to other aspects that would reduce the levels of tax evasion as well Suggesting some future studies on other factors that were not covered by the research.